2009
DOI: 10.1007/s11695-009-9845-3
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Laparoscopic Adjustable Gastric Bands on Esophageal Motility and the Gastroesophageal Junction: Analysis Using High-Resolution Video Manometry

Abstract: In LAGB patients, the LES is attenuated, although relaxes normally. Esophageal motility is preserved, although disrupted by overfilling the band. In the optimally adjusted LAGB, a delay in transit of liquids and semisolids through the esophagus and band is produced, along with an increase in repeated esophageal contractions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
88
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(92 citation statements)
references
References 21 publications
4
88
0
Order By: Relevance
“…Potential aetio logies include incompletely expressed or early achalasia, oesophageal wall stiffness from an infiltrative disease or cancer, vascular obstruction, sliding or para-oesophageal hiatal hernia, abdominal obesity or the effects of opiates 44 . Similar findings are found also in patients with dysphagia after restrictive, antireflux and bariatric procedures [45][46][47] . However, two series published in the past few years found that many patients with EGJOO were minimally symptomatic or asymptomatic, that in 20-40% of cases the 'disorder' resolved spontaneously, and that only 12-40% were treated (conservatively) as having achalasia 48,49 .…”
Section: Achalasia With Preserved Peristalsissupporting
confidence: 81%
“…Potential aetio logies include incompletely expressed or early achalasia, oesophageal wall stiffness from an infiltrative disease or cancer, vascular obstruction, sliding or para-oesophageal hiatal hernia, abdominal obesity or the effects of opiates 44 . Similar findings are found also in patients with dysphagia after restrictive, antireflux and bariatric procedures [45][46][47] . However, two series published in the past few years found that many patients with EGJOO were minimally symptomatic or asymptomatic, that in 20-40% of cases the 'disorder' resolved spontaneously, and that only 12-40% were treated (conservatively) as having achalasia 48,49 .…”
Section: Achalasia With Preserved Peristalsissupporting
confidence: 81%
“…This is based on successful patients consistently demonstrating an intraluminal pressure in the range of 25-30 mm Hg at the level of the LAGB. 7,19 This is despite variation in the device and the volume of saline within the LAGB, suggesting that the intraluminal pressure is important in mediating successful weight loss.…”
Section: Intraluminal Pressure Effectsmentioning
confidence: 99%
“…7,20 Repeated pressurizations progressively drive a swallowed bolus across the LAGB into the stomach. The time-limited-nature of peristaltic contractions causes episodes of flow to be interspersed by reflux events during which the bolus refluxes back into the esophagus-stimulating repeat peristalsis.…”
Section: Transit Mediated By Esophageal Peristalsismentioning
confidence: 99%
See 1 more Smart Citation
“…24 Burton studied the mechanism of action of the adjustable gastric band, which is considered the model of the restrictive principle. [25][26][27][28][29][30][31] He has accomplished detailed manometric and transit studies to reveal that the band is not restrictive in the sense commonly understood, but may rather induce diminished nutrient intake and weight loss for other reasons.…”
mentioning
confidence: 99%